Pengaruh Sikap Kasih Sayang Guru Terhadap Perilaku Siswa Berbudi Pekerti dan Hasil Belajar Siswa di SMK Negeri 2 Mandau - Jerni Hidayah,S, Jerni; Risnawati; Muhammad Fikham (MGMP PAI SMP BINTAN, 2024)
This research aims to explain the influence of PAI teachers' loving attitudes on virtuous student behavior and student learning outcomes at SMK Negeri 2 Mandau. The method used in this research is a quantitative descriptive method. The sample in this study was taken as 8% of the 290 students of SMK Negeri 2 Mandau for the 2024/2025 academic year and a sample of 30 students was obtained. Data collection techniques used were questionnaires, attitude scales, and tests. The results of data analysis show that there is a positive and significant influence between the PAI teacher's affectionate attitude towards the characterful behavior of students. The higher the PAI teacher's affectionate attitude, the higher the virtuous student behavior. And there is also a positive and significant influence between the PAI teacher's loving attitude on student learning outcomes. The higher the influence of the PAI teacher's loving attitude, the higher the student learning outcomes.